Three new species of Loneura (Psocodea:’Psocoptera’:Ptiloneuridae) from Gorgona Island, Cauca, Colombia, with a new infrageneric classification - Aldrete, Alfonso N. García; Obando, Ranulfo González; Sarria, Fabio A. Sarria (Zootaxa, 2011)
Three related species of Loneura Navás, from Gorgona Island (Cauca, Colombia), are here described and illustrated. The types are deposited in the Entomological Museum of the Universidad del Valle (MUSENUV). A set of infrageneric groups within Loneura is proposed based on the structure of the male hypandrium and phallosome. The species of the genus are assigned to the groups recognized in this classification.